Curriculum orientation of Malaysian university educators in designing learning outcome-based curriculum - Nor Azman, Ady Hameme (2011)
The appropriate adoption of curriculum orientation when designing learning outcome-based curriculum is important in order to ensure the success of Outcomebased Education at Malaysian public universities. In regard to the necessity, a question is raised: Do public university educators adopt the appropriate orientation when designing such curriculum? Although Outcome-based Education is deemed to set the appropriate orientation on designing the learning outcome-based curriculum at public universities, the next challenge is how to make sure the orientation is adopted for such curriculum. For this reason, this study examines curriculum orientation when designing curriculum by administering questionnaires to 506 PhDqualified educators from 11 public universities in Malaysia. The questionnaire included items from the Curriculum Orientation Inventory along with questions that reflected age, gender, academic position, field of expertise and years of experience. Descriptive and inferential statistics such as ANOVA, the Pearson product-moment correlation coefficient, and MANOVA were used to answer the research questions. The results revealed that the ‘cognitive process’ (M=4.13, SD=0.52) and ‘curriculum as technology’ (M=4.11, SD=0.57) were the dominant curriculum orientations of Malaysian public university educators when designing curriculum. It indicates that university educators adopted the appropriate curriculum orientation when designing curriculum. This study also discovered moderate relationships among curriculum orientations such ‘curriculum as technology’ with ‘academic rationalism’ (r(504) =0.67, p < 0.01), ‘curriculum as technology’ with the ‘cognitive process’ (r(504) =0.67, p < 0.01), ‘curriculum as technology’ with ‘social reconstruction relevance’(r(504) = 0.47, p < 0.01), and ‘curriculum as technology’ with ‘selfactualisation/humanistic’ (r(504) = 0.49, p < 0.01). These relationships indicate that the design process of inculcating the eight domains of learning outcomes stipulated by the Malaysian Qualification Agency (MQA) is moderately oriented for efficiency.In addition, this study found no significant difference between males and females on their curriculum orientations when designing curriculum, especially on the ‘curriculum as technology’ curriculum orientation (F(5, 500)=1.02, p>0.05; Pillai’s trace=0.01; and partial eta squared=0.01). This shows that the orientation adopted by male and female educators when designing curriculum at public universities is the same towards the Outcome Based Education. Overall, it is hoped that findings of this study may create the awareness of how important curriculum orientation is in making sure the success of Outcome-based Education as well as guidelines for university educators’ training on how to adopt the required orientation when designing learning outcome-based curriculum more efficiently in the future. It is also hoped that the findings of this study can promote later studies on understanding the aspect of curriculum orientation rather than too focused on the managerial and practical aspects of curriculum when designing as well as the other domains of curriculum.